Pengaruh Board Monitoring Dengan Moderasi Political Connection Terhadap Audit Fee - Iman Harymawan; Marcelina Sanjaya (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2021)
This study aims to determine the relationship between board monitoring and audit fees with political connections as a moderating variable. This study uses 1,117 observations covering companies listed on the Indonesia Stock Exchange in 2010-2018 except companies in the banking, financial sectors and companies that do not disclose audit fees in their report. This study uses multiple linear regression through STATA 14.0 software to test hypotheses. This study found that the board of commissioners monitoring and the board of directors monitoring have a significant positive relationship on audit fees, the existence of political connections in the company also gives a positive relationship on audit fees and strengthened the relationship between the board of commissioners monitoring and the board of directors monitoring on audit fees. This study is expected to inform stakeholders regarding board monitoring and political connections in audit fees paid by companies.